Diseño de una estrategia para el tratamiento de aguas de retorno de yacimientos no convencionales para su aplicabilidad en Colombia según la resolución 0631 del 2015 y la normas ASTM 1193 del 2011 (2022)
The treatment of flowback water is a very sensitive issue in economic and environmental terms when talking about the development of unconventional reservoirs, in Colombia the main concern has to do with the amount of water used for the development of this type of reservoirs and also what happens to that water when the hydraulic stimulation process ends.